Insomnia Prevalence among Italian Night-Shift Nurses - Nicola Ielapi; Michele Andreucci; Umberto Marcello Bracale; Davide Costa; Egidio Bevacqua; Andrea Bitonti; Sabrina Mellace; Gianluca Buffone; Stefano Candido; Michele Provenzano; Raffaele Serra (MDPI AG, 2021)
Background. Insomnia is one of the major health problems related with a decrease in quality of life (QOL) and also in poor functioning in night-shift nurses, that also may negatively affect patients' care. The aim of this study is to evaluate the prevalence of insomnia in night shift nurses. This observational online web-based survey using Google®® modules specifically aimed to investigate the prevalence and risk factors for insomnia among Italian nurses. Methods. Data collection for this study lasted one month, with the questionnaire available from 1 March 2021 to 1 April 2021. Continuous variables were considered as either mean ± standard deviation (SD) or median and interquartile range (IQR) based on their distribution. Comparison among insomnia categories was assessed by one-way ANOVA or Kruskal-Wallis test according to variable distribution. Categorical variables were analyzed using chi-square test. Results. A total of 2355 responses were included in the final analysis, with 917 from the Northern zone, 815 from the Western zone, and 623 from the Southern zone of Italy. The prevalence of insomnia in the overall population was 65.4% (1524 out 2355 nurses suffered from insomnia). Conclusions. Nursing is a high-pressure profession, with heavy duties and high professional risks. We found an important prevalence of insomnia in night shift nurses, and we hope it may help to solicit further studies aimed to identify the risk factors for this working disorder among nurses.